Nursing interventions on eating patterns in nursing students - Aponte Aponte, Jennifer Carolina; Fernández Nieto, Miriam Ivonne (Enfermería Cuidándote, 2026)
Introduction: Dietary patterns are dietary behaviors that represent the selection, preparation, and consumption of food within a sociocultural framework. These practices are shaped by familial, cultural, and social influences and change throughout life.Objective: To identify the dietary patterns practiced by first-semester nursing students at the Technical University of Ambato.Materials and methods: A quantitative approach, with an observational design and descriptive scope, was used. The sample consisted of 105 first-semester nursing students selected using inclusion and exclusion criteria. A self-administered questionnaire was administered through the students' WhatsApp groups. Data were analyzed using Excel and SPSS, incorporating measures of central tendency and frequency distribution tables.Results: The main findings indicated that the majority of students follow partially adequate dietary practices. A notable deficiency in fruit and vegetable consumption was identified, along with a significant consumption of processed foods, such as chips, soft drinks, and confectionery. Furthermore, it was observed that most students consumed their main meals at home with their families.Conclusion: This study highlights the need to implement educational interventions and social support strategies aimed at improving students' eating patterns, thus promoting a more balanced and healthy diet.
Keywords: Eating Behavior; Healthy Eating; Lifestyles; Nursing Students